ChemInform Abstract: Copper‐Catalyzed Synthesis of a Highly Hydroxy‐Functionalized Benzo[e]indolizidine by Intramolecular N‐Arylation. Issue 1 (7th January 2014) - Cordero, Franca M.; Khairnar, Bhushan B.; Bonanno, Paola; Martinelli, Andrea; Brandi, Alberto
Abstract The enantiopure title compounds (VI) are synthesized by a straightforward strategy consisting of 1, 3‐dipolar cycloaddition, N‐O‐bond reduction, and cyclization reaction.